1989
DOI: 10.2307/1942603
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐Up and Top‐Down Impacts on Freshwater Pelagic Community Structure

Abstract: For freshwater pelagic ecosystems, the biomanipulation and cascading trophic interaction theories both predict that decreased piscivore populations will result in direct, short-term (a few years) increases in planktivore biomass, reductions in crustacean herbivore biomass, and increases in chlorophyll a concentration and phytoplankton biomass. An alternate view is offered by the bottom-up: top-down theory, which predicts that in eutrophic lakes changes in piscivore biomasses will have strong impacts on plankti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
242
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(268 citation statements)
references
References 57 publications
21
242
0
4
Order By: Relevance
“…Because phytoplankton species occupy a low trophic level, they are under relatively strict environmental or bottom-up control (Paszowski and Tonn 2000). Higher trophic levels, such as zooplankton that graze on phytoplankton, may be more strongly regulated by food-web interactions or top-down forces (McQueen et al 1989). In RDA, the finding that nutrient supply is the dominant factor influencing community composition of phytoplankton agrees with Longmuir et al (2007), who documented that trophic status of the lake was the strongest determinant of phytoplankton community structure in lakes in British Columbia, Canada.…”
Section: Discussionmentioning
confidence: 86%
“…Because phytoplankton species occupy a low trophic level, they are under relatively strict environmental or bottom-up control (Paszowski and Tonn 2000). Higher trophic levels, such as zooplankton that graze on phytoplankton, may be more strongly regulated by food-web interactions or top-down forces (McQueen et al 1989). In RDA, the finding that nutrient supply is the dominant factor influencing community composition of phytoplankton agrees with Longmuir et al (2007), who documented that trophic status of the lake was the strongest determinant of phytoplankton community structure in lakes in British Columbia, Canada.…”
Section: Discussionmentioning
confidence: 86%
“…As shown earlier for pelagic food webs (e.g., Sommer 1988;McQueen et al 1989), bottom-up and top-down forces simultaneously influence macrobenthic populations and communities (Menge et al 1997;Worm et al 2000a). Their relative strength, however, may vary under different environmental conditions.…”
mentioning
confidence: 74%
“…Although we admit that no valid generalizations can be drawn from a study involving two sites, we think that our results match similar patterns that emerged in different ecosystems. For example, it was proposed that in lake ecosystems, as productivity increases, top-down control at lower trophic levels should weaken and bottom-up control should become more important (McQueen et al 1989). Similarly, in saltmarsh ecosystems Van de Koppel et al (1996) observed that herbivore control of plant biomass weakened at high productivity levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, this predation will fluctuate in time with variations in population structure, as different sized individuals focus on different prey. It is accepted, however, that trophic cascades exert more influence on lower trophic levels in oligotrophic lakes (McQueen et al, 1989), and so the rather high nutrient concentrations in the study lake may counter such effects. Chlorophylla concentrations suggest that algae have slightly increased overall; this is still likely affected by the increase in benthic primary producers.…”
Section: Can the Impact Of Fish Introduction On The Aquatic Ecosystemmentioning
confidence: 96%